CONSTANT-Q CONFIGURATION OF 3-AXIS SPECTROMETER - Agus Purwanto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
CONSTANT-Q CONFIGURATION OF 3-AXIS SPECTROMETER. The constant-q method has been widely used in the 3-axis spectrometer, which requires more angles to be setup as compared to those of the diffractometer. Those angles are not natural variables in the physical quantities of interest for the dynamic properties of materials. As the physical quantities of interests are the energy and momentum transfer, those angles must be converted into the energy and momentum transfer. To the author’s knowledge, although this method has been known since around 1960’s, no literature sufficiently describes the details to provide the necessary equations. This paper elaborates the conversion by using the energy and momentum conservation with the vector and trigonometric consideration of the scattering processes in the reciprocal space. The angle values resulted from this conversion might be used to obtained the dispersion relation measurement by utilizing the 3-axis spectromenter.